1996
DOI: 10.1002/eji.1830260821
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and functional characterization of CD11c+ dendritic cell population in mouse Peyer's patches

Abstract: The antigen-presenting cell system in the gastrointestinal tract, one of three main sites (skin and lung being the others) of primary antigen contact, is poorly understood. Our study focused on dendritic cells (DC) as possible candidates for antigen uptake, processing and presentation in mucosal inductive sites, such as Peyer's patches (PP). To investigate the morphology, immunophenotype and stimulatory activity of intestinal DC, a procedure was developed to obtain a cell population by using collagenase digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 107 publications
(75 citation statements)
references
References 22 publications
5
69
0
1
Order By: Relevance
“…Conventionally it is assumed that the APC involved in the uptake and presentation of intestinal antigens are in Peyer's patches (PP) [5], and the PP contain unusual subsets of DC, some of which can produce IL-10 and drive the production of IL-10 by antigen-specific T cells [6]. These findings therefore support the idea that PP DC may be important for the generation of T reg and oral tolerance.…”
Section: Introductionmentioning
confidence: 74%
“…Conventionally it is assumed that the APC involved in the uptake and presentation of intestinal antigens are in Peyer's patches (PP) [5], and the PP contain unusual subsets of DC, some of which can produce IL-10 and drive the production of IL-10 by antigen-specific T cells [6]. These findings therefore support the idea that PP DC may be important for the generation of T reg and oral tolerance.…”
Section: Introductionmentioning
confidence: 74%
“…These include different types of conventional APCs like dendritic cells (17)(18)(19)(20)(21)(22)(23)(24)(25), macrophages (26,27), and B cells (28) along with other putative APCs such as intestinal epithelial cells (29). We have found that the APC responsible for the presentation of oral OVA to both CD4 ϩ and CD8 ϩ T cells in the GALT is of bone marrow origin because T cell proliferation was evident only in chimeric mice in which the bone marrow-derived compartment expressed the correct MHC haplotype (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…We used iodixanol as the ultracentrifugation gradient medium because this agent has been successfully used to isolate cells [12,13], organelles [14,15], macromolecules [16,17], and viruses [18][19][20][21][22]. Using iodixanol discontinuous density ultracentrifugation followed by sizeexclusion chromatography, we successfully isolated and purified both RGD-modified and non-RGD-modified adenovectors with a degree of purity and infectivity comparable to that of adenovectors purified by traditional 2× CsCl ultracentrifugation.…”
mentioning
confidence: 99%